Abstracts and Afterparties: Surviving the EHPS conference in the best way possible - Yil Engbersen-Severijns; Ciska Hoving (European Health Psychologist, 2026)
Attending a scientific conference can be inspiring to some and highly stressful for others. Stress may not only arise from presenting, but also from the social and cognitive demands of being surrounded by others, navigating a tight schedule and managing networking expectations. At the same time, conferences offer valuable opportunities for learning, collaboration and identity-building within one’s academic community, contributing to professional development. This reflection paper provides guidance for preparing and attending a conference. We outline practical considerations and personal experiences related to four areas: (1) preparations, (2) program, (3) networking and (4) participating in social activities.